Hipernatremia dan Penatalaksanaanya - Setyawan, Yuswanto (Universitas Sam Ratulangi, 2021)
Abstract: Hypernatremia could be caused by loss of water (increased loss or decreased intake), and although rarely, due to over intake of natrium. Patients who are at risk of hypernatremia are those with disturbance of thirst or limited access of water. Several factors that could cause hypernatremia especially among geriatric patients are, as follows: change of thirst stimuli, decreased ability to concentrate urine, and decreased total body water. Clinical signs of hypernatremia are usually not specific, however, patients tend to become symptomatic if hypernatemia occurs acutely. Hypernatremia clinical signs are mostly neurological related to the severity and the change of serum sodium concentration. Complications of hypernatremia are inter alia shrinkage of brain tissue due to the movement of water from intracellular to extracellular fluid which results in injury of brain vessels, bleeding in the brain, and a variety of neurological signs due to brain involovement which could lead to death. Management of hypernatremia has to be carried out accurately and thoroughly because inaccurate or too-rapid correction could risk the occurrence of cerebral edema.Keywords: hypernatremia, total body waterÂ Â Abstrak: Hipernatremia dapat disebabkan oleh kehilangan air (peningkatan kehilangan atau penurunan asupan) dan, walaupun jarang, karena kelebihan asupan natrium. Yang berisiko tinggi untuk hipernatremia ialah mereka dengan gangguan mekanisme rasa haus atau keterbatasan akses terhadap air. Berbagai faktor dapat menyebabkan hipernatremia terutama pada geriatri seperti perubahan rangsangan haus, berkurangnya kemampuan pemekatan urin, dan berkurangnya total body water. Gejala klinis hipernatremia biasanya tidak spesifik namun pasien cenderung menjadi simtomatik saat hipernatremia terjadi secara akut. Gejala hipernatremia terutama bersifat neurologik terkait dengan tingkat keparahan dan kecepatan perubahan konsentrasi natrium serum. Komplikasi hipernatremia ialah antara lain penyusutan otak akibat perpindahan cairan intrasel ke ekstrasel yang dapat merobek pembuluh darah otak, pendarahan otak, dan berbagai gejala neurologik akibat keterlibatan otak, yang dapat berakhir fatal. Penatalaksanaan hipernatremia perlu dilakukan dengan cermat karena penanganan yang tidak tepat atau koreksi yang terlalu cepat dapat berisiko terjadinya edema serebri.Kata kunci: hipernatremia, total body water